Democratic memory and picturebooks at initial teacher training - Luna Velasco, Úrsula; Serrano-Mariezkurrena, Amaia; Echeberria Arquero, Berta (Clio. History and History Teaching, 2024)
This paper presents the GATAI project, an interdisciplinary educational innovation initiative developed in the third year of the Primary Education Degree at the University of the Basque Country (UPV/EHU). The project explores the use of controversial issues and picture books in teacher training. University students designed and delivered classroom sessions for primary school children, focused on reading and interpreting picture books that address democratic memory. These sessions were carried out across 25 primary school classes in four schools in Gipuzkoa. The findings highlight the considerable potential of these literary resources in addressing the topic of democratic memory in primary education, as well as their role in training future teachers to design didactic proposals using picture books in primary school settings.
Keywords: controversial issues; democratic memory; historical memory; picturebooks; teacher training; elementary education; literary education